2010
DOI: 10.1108/17511871011061046
|View full text |Cite
|
Sign up to set email alerts
|

Leader‐member exchange as a significant correlate of organizational and occupational sportsmanship behaviors in a health services setting

Abstract: Purpose -The purpose of this study is to test for the distinctiveness of organizational versus occupational sportsmanship behavior, and then to investigate the relationship of leader-member exchange (LMX) to each. Design/methodology/approach -A sample of 223 matched nurse-supervisor dyads working for a hospital in Oman was surveyed. Analytic methods included factor analysis and regression. Findings -Organizational sportsmanship behavior was distinguishable from occupational sportsmanship behavior. LMX or the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…(2008) found that high‐quality LMX was positively associated with their perceptions of supervisor support and organizational citizenship behaviour in nurses. Blau et al. (2010) reported similar finding in a sample of nurses in Oman however, LMX quality was related to nurses’ sportsmanship behaviour or willingness to tolerate minor inconveniences.…”
Section: Related Researchsupporting
confidence: 62%
See 2 more Smart Citations
“…(2008) found that high‐quality LMX was positively associated with their perceptions of supervisor support and organizational citizenship behaviour in nurses. Blau et al. (2010) reported similar finding in a sample of nurses in Oman however, LMX quality was related to nurses’ sportsmanship behaviour or willingness to tolerate minor inconveniences.…”
Section: Related Researchsupporting
confidence: 62%
“…2008, Laschinger et al. 2009, Blau et al. 2010, Han & Jekel 2011) although only the Laschinger et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…emphasized that lack of sportsmanship may result from the following factors: lack of specific job descriptions, absence of teamwork, frequent conflicts among team members during their communication, employment staff with insufficient skills and training , obligation to work with insufficient materials, hard working conditions, excessive working hours, inability to enjoy legal rights, insufficient wages, and lack of safety measures. [30][31][32][33] Moreover, this study showed a strong positive high significant correlation between overall organizational trust and overall OCBs as perceived by staff nurses. This result can be justified that there had been a high significant difference between all dimensions of organizational trust and organizational citizenship behaviors.…”
Section: Discussionmentioning
confidence: 85%
“…However Altuntas & Baykal's (41) study performed in Turkey on nurses and found the mean OCB scores of sportsmanship have a higher than average level for conscientiousness. And Blau et al, (42) study regarding sportsmanship behaviors in hospital nurses in Oman and indicated the mean of grades for nurses in respected questionnaires in both job and organizational factors was higher than the overall mean. Therefore Tabarsa et al, (43) pointed to high level of OCB among nurses in a hospital as a result the hospital could maintain a better performance in providing care and health services by employing more efficient work forces.…”
Section: Resultsmentioning
confidence: 99%